2009
DOI: 10.1038/nrclinonc.2009.18
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to consider a role for MRI before prostate biopsy?

Abstract: The use of MRI in prostate cancer management is controversial and current guidelines underplay its role. Technological advances over the past 5 years, however, demand a re-evaluation of this position. In this article, we propose an increased use of MRI, not only in those with a diagnosis of prostate cancer but also for men before a prostate biopsy. The use of MRI before a biopsy can serve as a triage test in men with raised serum prostate-specific antigen levels, in order to select those for biopsy with signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
188
1
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(198 citation statements)
references
References 91 publications
1
188
1
8
Order By: Relevance
“…Studies using whole-mount histology as the reference standard have reported T2-weighted MRI scans with broad spectrums of sensitivity ranging between 37% and 96%. 22 The wide variation in results is a consequence of equipment, patient selection, experience and the accuracy of pathological correlation. 23 In addition, interobserver variability for the reference of each finding is also likely to affect the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using whole-mount histology as the reference standard have reported T2-weighted MRI scans with broad spectrums of sensitivity ranging between 37% and 96%. 22 The wide variation in results is a consequence of equipment, patient selection, experience and the accuracy of pathological correlation. 23 In addition, interobserver variability for the reference of each finding is also likely to affect the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This concept was advocated by Ahmed et al 108 Hambrock et al has shown that MRI-targeted biopsies can detect PCa in areas outside the peripheral zone or locations not biopsied in normal schemes, in particular the anterior part of the gland. 109 In that study, they utilized MRI to localize PCasuspicious areas followed by a median of four cores.…”
Section: Role Of Magnetic Resonance Imaging Targeted Biopsymentioning
confidence: 99%
“…[7][8][9] Results from the PROMIS study favour the use of upfront prostate mpMRI to triage biopsy-naive men when compared to systematic 10-12-core biopsy. 10 Other studies have shown the superiority of MRI-targeted biopsy compared to systematic 12-core biopsy, particularly in patients with previous negative biopsy.…”
Section: Introductionmentioning
confidence: 99%